Standardization Of Payakumbuh Galamai Recipes In Harau, Lima Puluh Kota Regency - Putri, Tivany; Gusnita, Wiwik (Universitas Negeri Padang, 2022)
Galamai Payakumbuh in Harau Subdistrict, Lima Puluh Kota Regency still uses material estimates so that the resulting galamai has different material qualities. This study aims to convert galamai recipes into unit sizes (grams). The method used is a mixed method (mixed method). Qualitative data sources were obtained from 11 people who are experts in making galamai and quantitative data sources were obtained from 10 community panelists who know about galamai and 5 panelists from UNP's Catering lecturers. Qualitative data collection techniques using techniques, namely: data reduction, data presentation and conclusions, while the three quantitative data collection using organoleptic tests. Based on the research conducted, the galamai recipe was obtained, the materials and tools used, the processing process and the expected quality of the galamai. The recipes obtained were then converted and organoleptic tests were carried out to obtain the quality of the galamai including: the shape of the galamai (neat and uniform), the color of the galamai (dark brown), the aroma of the galamai (fragrant), the texture of the galamai (chewy and uniform) and the taste of the galamai (sweet).